Quality Assurance in UML Models: A Review of Related Literature - Dalisay, Ferdinand V. (Asian Journal of Multidisciplinary Studies, 2018)
The quality UML models directly affects the quality of the software or application being developed. Therefore, quality assurance in UML models should be regarded as an important niche. This paper describes a literature review of peer-reviewed journal articles published from 2012 through 2018 on the quality of conceptual models written in UML.